Predicting the effects of rare genetic variants on oncogenic signaling pathways: A computational analysis of HRAS protein function - Ali, Sadaqat; Ali, Usman; Qamar, Adeem; Zafar, Imran; Yaqoob, Muhammad; Ain, Qurat ul; Rashid, Summya; Sharma, Rohit; Nafidi, Hiba-Allah; Bin Jardan, Yousef A.; Bourhia, Mohammed (Frontiers in Chemistry, 2023)
The HRAS gene plays a critical role in regulating fundamental cellular processes such as cell division, differentiation, and apoptosis. Its misregulation has been associated with the development of a variety of cancer types. Within the coding region of HRAS, nonsynonymous single nucleotide polymorphisms (nsSNPs) can lead to detrimental mutations that interfere with the normal protein function. In this study, our objective was to prognosticate the effects of rare genetic variants on HRAS protein function using a variety of computational tools. From among 50 nsSNPs, we identified 23 that were projected to be deleterious, and out of these, 10 nsSNPs ([G60V], [G60D], [R123P], [D38H], [I46T], [G115R], [R123G], [P11OL], [A59L], and [G13R]) were singled out as having the most ruinous impacts. We executed molecular dynamics simulations to explore the consequences of these nsSNPs on the stability, flexibility, and compaction of the HRAS protein. Our findings demonstrate the potential function of nsSNPs in upregulating HRAS expression and contributing to oncogenic signaling pathways. This study presents a well-crafted in silico approach for scrutinizing HRAS-associated nsSNPs and offers insights into the mechanisms underlying their influence on HRAS protein function.